Analysis of overpressure mechanisms in a field of southwestern Malay Basin - Satti, I.A. (Offshore Technology Conference, 2014)
This study demonstrates the utilization of wireline logs for pore pressure mechanism analysis in a field of southwestern Malay Basin. Development of overpressures means that fluid movement in the pores is retarded both vertically and laterally. In many Tertiary basins overpressure is mainly generated by compaction disequilibrium due to high deposition rate and low permeability in shales. In the Malay Basin, temperature and high heat flow also plays an important role in generating overpressure at shallow depth as geothermal gradient is very high 40-60 Â°C/km. Overburden pressure is calculated for all the wells using density log. Pore pressure profiles, cross plots of sonic velocity-vertical effective stress and sonic velocity-density are used to derive the overpressure generating mechanisms. The results obtained from the cross plots of 10 wells reveals that in the study area overpressure is generated by both primary and secondary mechanisms such as compaction disequilibrium and fluid expansion. Overpressure magnitude analysis suggests that overpressure generated by the secondary mechanism is very high as compare to primary mechanism. Eaton's method with exponent 3 gives good prediction where overpressure is the result of compaction disequilibrium mechanism but under-predicted the high pore pressures where fluid expansion mechanism is also present. However, the overpressures are predicted quite well by using higher Eaton exponent of 5 for fluid expansion mechanism. Bowers method is also used for pressure prediction and it gives reasonably good prediction in high overpressure zone by using the unloading parameter (U) of 6. Copyright 2014, Offshore Technology Conference.